Lubomyra Hnatiuk: THE ASPECT OF AUTHOR’S SENSORY IN THE LITERARY WORK “THEATER” BY S. MAUGHAM - Hnatiuk, Lubomyra (Linguistic Bulletin (Movoznavchyi Visnyk), 2022)
Аbstract. Introduction. The article analyzes the aspect of author’s sensority in the novel “Theater” by S. Maugham. The semantic modeling of the author’s sensority in the semantics of the literary text is considered, and the features of its implementation are determined. Reference has been made to the subject and object of the research of the aspect of author’s sensority in the literary work “Theater” by S. Maugham. Purpose. The purpose of the study is the linguistic analysis of the measurement of the author’s sensory on the material of the literary text. Methods. A descriptive-analytical method was used, as well as the method of analysis and synthesis. The method of representative sampling was used to select factual linguistic material of the study. During the direct analysis of the semantic potential of the selected lexical units, the method of conceptual and component-semantic analysis, the method of semantic-cognitive analysis and the method of cognitive modeling were used. Results. It is determined that perceptual images are linguistic markers of actualization of the author’s sensory in the semantics of the text. They become specific authorial reflections of the world created by the writer with the help of sensory images. Perceptual images are correlated with the work of the author’s senses and are transmitted through sensory – significant linguistic means. The reason for using sensory language in fiction is to strengthen its emotional mood, the ability to make visual images even more visible through synesthesia – a special way of perception, in which some concepts, phenomena and states are added additional qualities: smell, taste, color, texture, sound tone etc. Originality. Despite the systematic and purposeful scientific research in the field of research of the author’s sensory of the textual world, some aspects of this phenomenon still remain insufficiently studied by scientists in the field of lexicology. In this regard, the linguistic analysis of the dimension of the author’s sensory of the work of art, as well as determining the features of its implementation in the semantics of the literary text are currently relevant and significant. Conclusions. The article highlights that S. Moem actively uses perceptual vocabulary, which increases the sensory tension of perception and creates more accurate artistic images. The language of Moem’s work “Theater” embodies the mental processes of perception of the world through sensory modes of perception (visual, auditory, tactile, olfactory, gustatory, kinetic, kinesthetic and vestibular), which verbalize the perceptual knowledge of the author. We offer for the future consideration of further research in a more detailed study and comprehensive study of aspects of the measurement of the author’s sensory artistic text